La ley de Okun en el Perú: 1970-2000 - Garavito, Cecilia (2003)
The objective of this work is to analyze the existing relation between employment,unemployment and production, by means of the estimation of the Okun coefficient for thePeruvian Economy. A previous step consists in the estimation of the employment-productionelasticity. Both parameters are important elements for macroeconomic policy design, and theevaluation of its effects on employment and welfare. Based on a cointegration analysis we find a positive long-term relation between the employment rate and Lima's GDP throughout the period,where the employment rate rises in 0.0288 percentage points for a rise of 1000 nuevos soles of1979. We also estimate an Okun coefficient of 0.0845, its low value is only comparable withthose of Japan, Bolivia and Argentina. In Peru's case, the reason for this low coefficient can befound in the procyclical behavior of the labor force, and in the fact that workers retire from thelabor market when they lose their post. We also find that the rate of growth of the GDP must beat least of 3.31% in order to keep the unemployment rate from rising, and of about 11% to lowerthe unemployment rate in one point. Finally, we estimate recursive Okun coefficients based onthe cyclical components of the series, which gives us a range between 0.02 and 0.12 for thewhole period.